I think this gave us the courage to make ourselves heard. About the initiative of a few students in a compulsory school in Iceland to improve the curriculum - Hreinsdóttir, Anna Magnea (Menntavísindasvið Háskóla Íslands, 2022)
The aim of this study is to shed light on how a few 15-year-old students called for changes in the National Curriculum for Compulsory Schools in Iceland which they found obsolete to some extent. The objective, furthermore, is to analyse the impact of their proposals on their peers, their school, the municipality where the school is located and on government policy making. By examining the students’ initiative, the research seeks to understand whether anyone listens to students’ views, actions, and activities and whether their opinions can lead to changes in the content of learning and teaching. The research questions asked what made a few young students in a compulsory school in Iceland call for changes to the National Curriculum Guide for Compulsory Schools and what the effect of their call for change was. Students’ voices and their influence have attracted researchers’ attention in recent years, as young people have become increasingly involved in the public arena. The theoretical framework is based on theories and studies on children’s social activism, the “Greta Thunberg Effect” and on children’s voices, and agency in line with the United Nations Convention on the Rights of the Child. The study also reflects on the impact of the students’ initiative and the adultism that surfaces when children want to take matters in their own hands, on the pretext of knowing better and protecting them.The research is based on available information about the initiative of the students, the association Our Education System, formed by the students and media coverage of its proposals and actions. Further sources are a group interview with the students that formed the board of the association, and interviews with the school administrator and the department head of education at Hafnarfjarðarbær, where the compulsory school the students attended is located. A question-frame and research emphases were prepared with the aim of the study in mind. Permits were obtained from the participants and the parents of the students. According ...